Synergies between plant antioxidant blends in preventing peroxidation reactions in model and food oil systems - Irwandi, J.; Che Man, Y. B.; Kitts, D. D.; Bakar, J.; Jinap, S. (Wiley, 2000)
A study was conducted to investigate the oxidative behavior of various mixtures of rosemary, sage, and citric acid in a linoleic acid model system by oxygen consumption measurement and in a palm olein system by differential scanning calorimetry (DSC) analysis. Response surface methodology was used to optimize the use of the mixtures. Results showed that rosemary and sage were two important factors for the protective index (PI). The two antioxidants were highly significantly (P<0.001) in influencing PI values. There was a significant (P<0.01) synergistic effect between rosemary and sage on PI values. Citric acid was also found to be significant (P<0.05) for PI. With respect to onset time (To), all three antioxidants were significant (P<0.05). However, no significant interaction among antioxidants was found for To. Mathematical models for both PI and To could be developed with confidence. The R2 values for PI and To were 0.992 and 0.926, respectively. A combination of 0.078% rosemary, 0.067% sage and 0.037% citric acid was the optimal combination for PI, whereas a combination of 0.068% rosemary, 0.075% sage, and 0.039% citric acid was required to reach the optimal To value.